2022
DOI: 10.1016/j.psj.2021.101572
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin ameliorates APEC-induced intestinal injury in chicks by inhibiting the PI3K/AKT-mediated NF-κB signaling pathway

Abstract: Avian pathogenic Escherichia coli ( APEC ) is the causative agent of avian colibacillosis. Baicalin ( BA ) possesses multiple pharmacological effects, but the mechanism underlying its activity in APEC-induced intestinal injury remains unknown. This study aims to investigate the protective effects and possible mechanism of BA against APEC-induced intestinal injury. Sixty 1-day-old chicks were randomly divided into 4 groups: the control group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Activation of the PI3K/AKT pathway can increase the production of MMP through several downstream targets, of which NF-κB is considered a key regulator, , and activation of NF-κB can lead to the release of different types of inflammatory factors, ultimately causing intestinal inflammation . In addition, upon stimulation of cytokine receptors and other receptors, the membrane protein PI3K can directly or indirectly induce phosphorylation of AKT, which, in turn, activates NF-κB . In this study, the mRNA expression levels of PI3K, Akt, and NF-κB increased notably in the oil control group, and the phosphorylation levels were upregulated; however, the mRNA and phosphorylation levels of PI3K, AKT, and NF-κB were significantly decreased by PSNB treatment.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Activation of the PI3K/AKT pathway can increase the production of MMP through several downstream targets, of which NF-κB is considered a key regulator, , and activation of NF-κB can lead to the release of different types of inflammatory factors, ultimately causing intestinal inflammation . In addition, upon stimulation of cytokine receptors and other receptors, the membrane protein PI3K can directly or indirectly induce phosphorylation of AKT, which, in turn, activates NF-κB . In this study, the mRNA expression levels of PI3K, Akt, and NF-κB increased notably in the oil control group, and the phosphorylation levels were upregulated; however, the mRNA and phosphorylation levels of PI3K, AKT, and NF-κB were significantly decreased by PSNB treatment.…”
Section: Discussionmentioning
confidence: 49%
“…The PI3K/AKT signaling pathway also plays an important role in the development of inflammation. Activation of the PI3K/AKT pathway can increase the production of MMP through several downstream targets, of which NF-κB is considered a key regulator, , and activation of NF-κB can lead to the release of different types of inflammatory factors, ultimately causing intestinal inflammation . In addition, upon stimulation of cytokine receptors and other receptors, the membrane protein PI3K can directly or indirectly induce phosphorylation of AKT, which, in turn, activates NF-κB .…”
Section: Discussionmentioning
confidence: 99%
“…In NF-kB signaling pathways, IKK activate NF-kB by phosphorylating the IKKα or IKKβ in an IKKγ-dependent manner which is triggered by release and interaction of inflammatory mediators (cytokines), endo/exo toxins, and proteins serving as receptors of the antigens ( Li et al, 1999 , Chen and Greene, 2004 , Liang et al, 2014 , Lai et al, 2017 , Liu et al, 2019 , Cheng et al, 2021 ). Studies reported in knock-out mice that, in the developing liver (embryonic stage) high rate of embryonic mortality in IKKβ-deficient mice is mediated by extensive liver apoptosis because of defective TNF or IL signaling to NF-κB (Liu, 2019 #476; Lai, 2017 #455).…”
Section: Introductionmentioning
confidence: 99%
“…Its use first appeared in the Han Dynasty classic ShenNongBenCaoJing, which recorded its efficacy in treating lung and liver diseases [ 1 ]. Baicalin, one of the flavonoids purified from S. baicalensis , can exhibit anti-bacterial [ 2 ],anti-inflammation [ 3 ], analgesic effects [ 4 ]. In the field of stomatology related research, baicalin has been shown to significantly enhance type I collagen and protein synthesis in gingival fibroblasts [ 5 ].…”
Section: Introductionmentioning
confidence: 99%